2015
DOI: 10.1093/mnras/stu2728
|View full text |Cite
|
Sign up to set email alerts
|

The HU Aqr planetary system hypothesis revisited

Abstract: We study the mid-egress eclipse timing data gathered for the cataclysmic binary HU Aquarii during the years 1993-2014. The (O-C) residuals were previously attributed to a single ∼ 7 Jupiter mass companion in ∼ 5 au orbit or to a stable 2-planet system with an unconstrained outermost orbit. We present 22 new observations gathered between June, 2011 and July, 2014 with four instruments around the world. They reveal a systematic deviation of ∼ 60-120 seconds from the older ephemeris. We re-analyse the whole set o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 70 publications
0
68
0
Order By: Relevance
“…Several trial runs of the observations revealed many local minima which could easily trap our Markov chains depending on our set of initial conditions. It is possible, therefore, that our results are based on samples from a local rather than the true global minimum, which, based on the results of Goździewski et al (2013), would not be too surprising.…”
Section: Stability Modellingmentioning
confidence: 98%
See 4 more Smart Citations
“…Several trial runs of the observations revealed many local minima which could easily trap our Markov chains depending on our set of initial conditions. It is possible, therefore, that our results are based on samples from a local rather than the true global minimum, which, based on the results of Goździewski et al (2013), would not be too surprising.…”
Section: Stability Modellingmentioning
confidence: 98%
“…A Bulirsch-Stoer integrator, similarly used by Goździewski et al (2013) in their detailed analysis of the ν Oct system, is appropriate given the assumed geometry includes a nearby massive secondary-star perturber, and which makes for instance the 'hybrid' integrator unsuitable. Nothing remained dynamically stable past our integration baseline.…”
Section: Stability Modellingmentioning
confidence: 99%
See 3 more Smart Citations